Strategi Pengembangan Paket Wisata Bahari Berbasis Kearifan Lokal Di Taman Nasional Bunaken Untuk Meningkatkan Daya Saing Destinasi Sulawesi Utara - Bet El Lagarense; Nelson Alexander; Agustinus Walansendow (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2025)
The development of marine tourism in Bunaken National Park holds significant potential in enhancing the competitiveness of North Sulawesi’s tourism destinations. However, challenges such as ecological pressures, limited community involvement, and inadequate integration of local wisdom into tourism packages hinder destination growth. This study aims to formulate strategies for developing marine tourism packages based on local wisdom to enhance destination competitiveness using participatory approaches, community empowerment, and sustainable conservation. A qualitative approach was adopted, including case study analysis and stakeholder interviews (managers, MSMEs, and tourists). Findings suggest that integrating local cultural elements, enhancing human resource capacity, digital marketing strategies, and multi–stakeholder collaboration are essential to improving destination competitiveness. Strategic recommendations are proposed to support more innovative, inclusive, and sustainable tourism package development. The results contribute to policy development for marine tourism in Indonesia’s marine conservation areas.